2020
DOI: 10.1108/ijrdm-04-2020-0142
|View full text |Cite
|
Sign up to set email alerts
|

Consumer responses to online fashion renting: exploring the role of cultural differences

Abstract: PurposeThe purpose of this study is to explore consumer behaviour in the context of online fashion renting by applying the theory of reasoned action (TRA) to online fashion rental services and comparing how consumers perceive online fashion renting in terms of its ecological importance and compatibility with the cultures of the USA and China.Design/methodology/approachQuantitative research was conducted, and 646 data sets were collected from a research firm within three weeks. Prior to launching the main surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 57 publications
0
21
1
Order By: Relevance
“…, 2012), there has been little research on the effect of model type on fashion consumer behaviour. This paper contributes substantially to this literature and further expands the understanding of the effect of visual information and static images on consumers, particularly with respect to the visual information anchor (Lee and Huang, 2021; Xue et al. , 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…, 2012), there has been little research on the effect of model type on fashion consumer behaviour. This paper contributes substantially to this literature and further expands the understanding of the effect of visual information and static images on consumers, particularly with respect to the visual information anchor (Lee and Huang, 2021; Xue et al. , 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 87%
“…Although there have been numerous studies on the effect of visual information and e-retail information quality on consumers (Hsu et al, 2012), there has been little research on the effect of model type on fashion consumer behaviour. This paper contributes substantially to this literature and further expands the understanding of the effect of visual information and static images on consumers, particularly with respect to the visual information anchor (Lee and Huang, 2021;Xue et al, 2020). In this work, we used approach behaviour to represent consumer behaviour rather than willingness to buy.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 99%
“…Cultural differences may impact our findings. First, rent stigma, which has been shown to be prevalent in multiple countries (in United States, Cohen et al, 2009 ; in United Kingdom, Foye et al, 2018 ; in Israel, Kricheli-Katz and Posner, 2020 ), may be weaker in some cultures ( Lee and Huang, 2021 ). Second, our samples in the United States are fairly pro-ownership, in general.…”
Section: Discussionmentioning
confidence: 99%
“…This may depend on the novelty fashion rental embodies for most consumers, when an activity is not familiar, customers tend to collect information and rely on advice from friends to assess its potential convenience (Schepers and Wetzels, 2007). Differences were also highlighted between American and Chinese consumers on the perceived risks and enjoyment of fashion rental, as well as on attitudes towards renting (Lee and Huangh, 2020; Pantano and Stylos, 2020; Lang et al , 2019). Furthermore, by exploring the benefits and fears of customers towards fashion rental (Lang et al , 2020; Mukendi and Henninger, 2020), it was found that as customers frequently use fashion items to show their social status (Yuan and Shen, 2019), fashion rental provides them with the opportunity to have access to luxury fashion items that they could not otherwise afford.…”
Section: Theoretical Backgroundmentioning
confidence: 99%